The Efficacy of Decalcified Freeze-Dried Bone Allograft With or Without Advanced-PRF (Platelet-Rich Fibrin) for Furcation Deficiencies - Mohamed H. Salama (Journal of Pharmacy and Bioallied Sciences)
Objective: To estimate the efficiency of advanced platelet-rich fibrin (A-PRF) with or without the combination of decalcified freeze-dried bone allograft (DFDBA) in furcation defects. Material and Methods: Twenty individuals with chronic periodontitis, with grade II furcation abnormalities, were included in this cross-sectional research. They were divided arbitrarily into Group I: DFDBA with A-PRF and Group II: DFDBA with 10 samples in each group. These grafts were applied to the defective sites. Radiographic measurements for average alveolar bone defect and clinical parameters, such as gingival index (GI), plaque index (PI), horizontal clinical attachment level (HCAL), and vertical clinical attachment level (VCAL), into the furcation defect were checked at baseline to six-month intervals. Results: Recession, relative vertical attachment level (RVCAL), and percentage of bone fill were observed to be improved in the test sites relative to the control, although these differences were not statistically significant. Conclusion: The combination of DFDBA with A-PRF is effective in comparison with DFDBA alone in the treatment of furcation defects.